From the standpoint of progressive law, the idea of legal protection for land deed officials in the electronic mortgage system - Sinaga, Nelly Azwarni; Nurlinda, Ida; Yamin, Muhammad; Zaidar, Zaidar (Edelweiss Applied Science and Technology, 2024)
The Electronic Mortgage Rights System was established through the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency number 5 of 2020. The Electronic Mortgage Rights System is an integrated electronic registration service for Mortgage Rights aimed at maintaining data and providing efficient and effective services in the registration of Mortgage Rights. However, this Electronic Mortgage Service has implications for the position and legal responsibilities of the Land Deed Official as stipulated in Article 20, paragraph (4) of the Regulation of the Minister of Agrarian and Spatial Planning / Head of the National Land Agency number 5 of 2020. Therefore, based on the concept of progressive legal theory, a Land Deed Official is entitled to legal protection from the substantive errors of a regulation that is less favorable. This research aims to examine the issues regarding how the concept of legal protection for Land Deed Officials within the electronic mortgage system is viewed from the perspective of progressive law. This research method is of a Juridical Normative nature with a prescriptive approach. Based on the research findings, it can be concluded that from the perspective of legal protection theory and progressive legal theory, it is incorrect to burden the Land Deed Official with legal responsibility for the accuracy of data and the validity of documents that were not created by them, but rather provided by the data and document owners who should be responsible for the accuracy of that data and the validity of those documents. It is also incorrect for the Land Deed Official to create and sign a "Statement" regarding the accuracy of data and the validity of documents uploaded through the electronic Mortgage Registration System, as this "Statement" should be made and signed by the Debtor and Creditor as the owners of the data and documents. Therefore, the Land Deed Official deserves legal protection from regulations that substantially do not favor them, as these impose responsibilities beyond their authority. Based on that conclusion, it is recommended to reconstruct Article 20 paragraph (4) of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Regulation number 5 of 2020, and to transfer legal responsibility to Debtors and Creditors as the parties involved in the Electronic Mortgage System, in order to build a legal framework that aligns with the future legal ideals in Indonesia, through a holistic approach that includes legal reform, institutional capacity building, and strengthening ethics, morals, and professionalism in positions.